RELIGIOUS MODERATION AND ITS IMPLEMENTATION AT ISLAMIC BOARDING SCHOOL IN EAST KALIMANTAN, INDONESIA - Sitti Sagirah; Abdul Waris; Muh. Agung Al Mansyah (Al-Qalam, 2024)
Implementing religious moderation in Islamic educational institutions, such as pesantren, has received important attention and massive efforts to strengthen moderate religious understanding in a multicultural society. This paper aims to analyze the implementation of religious moderation in pesantren in East Kalimantan. This paper is a qualitative research on pesantrens in East Kalimantan supplemented by relevant secondary sources. This paper reveals that the strategic steps taken by several pesantren in East Kalimantan, Indonesia, in implementing religious moderation are in the form of designing and implementing policies from pesantren leaders that support the creation of moderate attitudes and perspectives in the pesantren environment. These policies include instilling an understanding of religious moderation during the debriefing and introduction of new santri, doctrinalization at the graduation ceremony of santri, recruitment of strict and selective teaching staff, management of the pesantren unit curriculum that integrates religious moderation, determination of reference books for learning following the theology of ahlusunah waljamaah, strengthening value education and rules through a special curriculum, and others. This paper proves that the implementation of religious moderation in pesantren in East Kalimantan is not only through formal pesantren curricula but also through special pesantren curricula. Implementing religious moderation in pesantren in East Kalimantan requires policies of pesantren leaders that support the creation of moderate religious attitudes and perspectives in the environment. Thus, implementing religious moderation in pesantren in East Kalimantan cannot be separated from the curriculum and pesantren system.